2010
DOI: 10.3802/jgo.2010.21.1.3
|View full text |Cite
|
Sign up to set email alerts
|

Role of vascular endothelial growth factor inhibitors in the treatment of gynecologic malignancies

Abstract: This article reviews the history and current status of vascular endothelial growth factor targeted therapy for the most common gynecologic malignancies -epithelial ovarian, endometrial and cervical cancers. The biologic rationale for targeting vascular endothelial growth factor (VEGF) for these disease sites is well-founded, and pre-clinical studies have supported the development of anti-VEGF agents. Their classification, known mechanisms of action, unique toxicities and clinical development are herein explore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 59 publications
0
21
0
Order By: Relevance
“…Although several studies have targeted the VEGF family in ovarian cancer (15)(16)(17)(18), another effective approach for the treatment of various cancers are peptides derived from the TSR antiangiogenic domain of TSP-1 (19). Numerous studies have shown the antiangiogenic and antitumor effects of 3TSR (20)(21)(22) and ABT-510 (11,23,24) and have shown safety and efficacy in animal and human studies (12,13,25,26).…”
Section: Discussionmentioning
confidence: 99%
“…Although several studies have targeted the VEGF family in ovarian cancer (15)(16)(17)(18), another effective approach for the treatment of various cancers are peptides derived from the TSR antiangiogenic domain of TSP-1 (19). Numerous studies have shown the antiangiogenic and antitumor effects of 3TSR (20)(21)(22) and ABT-510 (11,23,24) and have shown safety and efficacy in animal and human studies (12,13,25,26).…”
Section: Discussionmentioning
confidence: 99%
“…During the past decade, role of VEGF targeted therapy was mentioned in gynecologic malignancies [17]. Most studies concentrated on ovarian cancer, while a few trials of cervical cancer are ongoing.…”
Section: Discussionmentioning
confidence: 99%
“…However, no difference in OS was observed. Bevacizumab treatment was well tolerated, with the major AEs attributed to chemotherapy 126 . In another Phase 3 trial, patients with EOC were treated with carboplatin and paclitaxel alone or in combination with concurrent bevacizumab.…”
Section: Monoclonal Antibodies For the Treatment Of Ovarian Cancermentioning
confidence: 99%